PENGELOLAAN KEUANGAN DANA DESA DI KECAMATAN TAROGONG KALER - Dewi, Nunik Lestari; Handayani, Rini; Jovita, Gabriella Alodia (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
The current village performance is supported by government policies related to the transfer of village funds, which aim to strengthen the quality of fiscal decentralization. Various infrastructure outputs produced from village funds are very beneficial for the survival of village communities. This article will discuss the financial management of village funds through planning, implementation, administration, reporting, and accountability activities. A case study in Tarogong Kaler District, Garut Regency. Descriptive research was carried out with questionnaire aids. The results show that villages in Tarogong Kaler District, Garut Regency, have implemented financial management of village funds in accordance with Permendagri Number 20 of 2018 and have fulfilled the principles of participation, accountability, and transparency.